Cartoon Image Encryption Algorithm by a Fractional-Order Memristive Hyperchaos - Shu-ying Wang; Jian-feng Zhao; Xiao-yan Wang; Li-tao Zhang (Journal of Electrical and Computer Engineering)
Based on the Adomian decomposition method and Lyapunov stability theory, this paper constructs a fractional-order memristive hyperchaos. Then, the 0–1 test analysis is applied to detect random nature of chaotic sequences exhibited by the fractional-order systems. Comparing with the corresponding integer-order hyperchaotic system, the fractional-order hyperchaos possesses higher complexity. Finally, an image encryption algorithm is proposed based on the fractional-order memristive hyperchaos. Security and performance analysis indicates that the proposed chaos-based image encryption algorithm is highly resistant to statistical attacks.